PERJUANGAN PANCASILA SEBAGAI DASAR BERDIRINYA NKRI - cici.nugraheni, cici.cicinugra (TEXTURA, 2020)
Pancasila as the basis for NKRI was not easily achieved. The founding fathers discussed causing a better intellectual debate that almost led to the verge of broken down. Finally it was agreed that the Jakarta Charter including Pancasila as the state. Apparently, with the Jakarta Charter did not necessarily dampen disputes; particularly with regard to the statement of divinity enforcing Islamic teaching for adherents. Then it was achieved a harmonious solution that takes into account the sensitivity of plurality in Indonesia and the above statement was replaced with a statement of Almighty God. Within the framework of hermeneutics, Pancasila is the text established and agreed upon by the founding fathers, was delivered to the Indonesian people, both Muslims and non-Muslims. After Pancasila was taken by Indonesian people, the founding father could not control fully to them who wanted to follow the reading. In fact, the Indonesian people responded differently according to the pre-understanding although coming from Muslim groups themselves. However, up to the present time, Pancasila remained exist in Indonesia.